Laboratory manual concepts in biology - Enger, Eldon D. (McGraw-Hill, 2003)
The exercises comprising this laboratory manual are intended to supplement the text Concepts in Biology, but they can be used with any introductory-level biology text. Laboratory exercises begin with a list of safety issues that students need to be aware of. These items identify caustic chemicals, equipment that needs special care or handling, and health or safety hazards a careless student may encounter.